Assessing depressive symptoms with the Borg centiMax Scale® in a Swedish sample of patients and students. Issue 2 (9th December 2019) - Borg, Elisabet; Jonsson, Frida; Mörtberg, Ewa
Abstract : The Borg centiMax Scale, is a psychophysically composed general intensity ratio scale, which could enable more precise inter‐ and intraindividual comparisons of the intensity of depressive symptoms. In the present study, the properties of the centiMax scale were examined in 38 patients with clinical depression and 109 students. Additionally, preliminary centiMax cut‐off scores for mild, moderate and severe depression were estimated. The psychometric properties of the centiMax were found to be satisfactory regarding internal consistency, convergent, discriminative and predictive validity. Moreover, the centiMax was demonstrated to provide meaningful comparisons of symptom intensity, which makes it possible to evaluate the relative importance of individual symptoms in a profile and make more precise comparisons within and between individuals. With regard to intraindividual comparisons, patients rated, for example, the intensity of feeling "guilt" twice as strong as feelings of "being punished, " and the intensity of "loss of pleasure" almost three times as strong as "being punished." With regard to interindividual comparisons, patients rated e.g., the intensity of "being punished" as 12 times stronger than controls, and the intensity of "worthlessness" about nine times stronger. In conclusion, the centiMax was shown to be reliable and valid for assessing depressive symptoms. The centiMax with level anchored ratio data, appears to be highly advantageous as it permits rather precise values of symptom intensity for intra‐ and interindividual comparisons that could be useful in the diagnostic process and in treatment planning.